Perbandingan Eksperimental dan Simulasi Frekuensi Pribadi pada Struktur Spindel CNC - Hoten, Hendri Van; Nurbaiti, Nurbaiti; Mainil, Afdhal Kurniawan; Silitonga, Jhonson Van (Jurnal Rekayasa Mesin, 2020)
The Research was about the comparison between experiment and simulation of natural frequency in CNC spindle. CNC spindle vibration will reduce machine tool performance. It could lead to the damage of the machine tool. The spindle structure unbalances of machine tools will cause vibration when it is operated. In the CNC machine, the spindle shaft vibration should be minimum. Based on this point, the natural frequency testing on the spindle shaft structure was carried out. The experiments were conducted by employing oscilloscope which could provide the vibration data in the time domain. The data was converted into the frequency domain using FFT. Measurements were carried out on 7 times of testing. Every one time of testing, 10 data were taken at each testing points. The tests were conducted at 10 testing points. Therefore, the total data obtained were 700 test data. The test results were then compared with the results of simulation modeling in 10 vibrate modes using Solidwork software. After testing and simulations were compared, 4 personal frequency values were obtained in the test that uses a measuring instrument and 6 personal frequency values could not be read. These were because the accelerometer used could not read up to 0 Hz frequency. Natural frequency obtained from simulations and tests were expressed in the percentage of errors. The largest error value in the 9th vibration mode measurement with a natural frequency was 2117.96 Hz with an error of 0.32%. The smallest error value was 0.11% with a natural frequency of 2995.79 Hz.